2020
DOI: 10.31234/osf.io/5f8kw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reading to bilingual preschoolers: An experimental study of two book formats

Abstract: Reading stories to children provides opportunities for word learning. Bilingual children encounter new words in each of their languages during shared storybook reading, but the way in which they encounter them can vary. We compared learning from two types of bilingual book materials: typical single-language books (i.e., two copies of the same book, each in a different language), and bilingual books (i.e., one copy of the book, with text in both languages on each page). Five-year-old French-English bilinguals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Oral language abilities influence literacy development for bilingual children (Bialystok, 2002), and it is possible that stronger oral skills in the dominant language impact children’s ability to learn new words in this language, as well as their interest in stories. However, recent experimental work that has directly tested word learning during shared storybook reading found that children were equally successful at learning dominant and non-dominant language words, suggesting that parents’ perception may not be accurate (Brouillard et al, 2020). Little research has directly compared bilingual children’s interest in being read to in each of their languages, but perceived or real differences could contribute to why families spend more time reading in the dominant than in the non-dominant language.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oral language abilities influence literacy development for bilingual children (Bialystok, 2002), and it is possible that stronger oral skills in the dominant language impact children’s ability to learn new words in this language, as well as their interest in stories. However, recent experimental work that has directly tested word learning during shared storybook reading found that children were equally successful at learning dominant and non-dominant language words, suggesting that parents’ perception may not be accurate (Brouillard et al, 2020). Little research has directly compared bilingual children’s interest in being read to in each of their languages, but perceived or real differences could contribute to why families spend more time reading in the dominant than in the non-dominant language.…”
Section: Discussionmentioning
confidence: 99%
“…Demographic characteristics of the sample are presented in Table 1. Participants were recruited through government birth lists, daycares, and community events, and completed the questionnaire as part of an experimental study of word learning in bilingual children (Brouillard, Dubé, & Byers-Heinlein, 2020). The sample size was determined based on the data available from that study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As described by parents in their open-ended responses, there are numerous approaches to the use of both languages while reading aloud that range from strict adherence to the language of the text of a book, to translating certain challenging words and phrases for the child, to changing the language of a story based on the comfort of the reader or the complexity of the extra-textual dialog that emerges. In previous research, we have found that predictable structured code-switching in the text of children's bilingual stories was helpful for older (5-year-old) DLLs in learning new vocabulary from stories (Read et al, 2020), while another recent study found DLL children were equally able to learn new vocabulary from full-translation bilingual books compared to monolingual books (Brouillard et al, 2020). However, neither of these recent bilingual storybook studies in which the books were read aloud by trained researchers tested the kinds of spontaneous extra-textual code-switching or translating that some parents in our sample reported using in their at-home shared reading.…”
Section: More On Language Mixing During Shared Readingmentioning
confidence: 94%
“…Indeed, a subset of preschool-age children performed better in identifying target objects (Kremin et al, 2022b) and learning novel words (Kaushanskaya et al, 2022) when the information was provided in mixed sentences. Preschoolers also benefit from language bridging in the classroom (use translation in children's first language to teach new words in the second language) and reading mixed-language books to acquire a second language (Brouillard et al, 2020;Read et al, 2021). In addition, children whose parents mixed languages frequently might become accustomed to language mixing and develop skills to navigate this linguistic situation.…”
Section: Positive Relationmentioning
confidence: 99%